Extending Theory of Planned Behavior to Understand Service-Oriented Organizational Citizen Behavior - Tsai, Kuang-Chung; Chou, Tung-Hsiang; Kittikowit, Santhaya; Hongsuchon, Tanaporn; Lin, Yu-Chun; Chen, Shih-Chih (Frontiers in Psychology, 2022)
The financial crisis of 2007-2008 and the COVID-19 pandemic have caused many enterprises to suffer great losses. Thus, companies have to take measures such as pays cut, furloughs, or layoffs, which caused dissatisfaction among employees and triggered labor disputes. Therefore, this study explores the service-oriented organizational citizenship behavior based on the decomposed theory of planned behavior in order to understand the behavioral intentions of employees through their mental states, job attitudes, subjective norms, and perceived behavioral control. This study conducted questionnaire surveys for employees in different industries, collected 281 valid questionnaires, and applied Structural Equation Model for the analysis. The results show: (1) Employees believe organizational justice in the organization is important, and when they feel treated fairly, their job attitudes and beliefs are enhanced. (2) Employees' job attitudes and beliefs support service-oriented organizational citizenship behavior, in other words, they have positive job attitudes and beliefs and will actively provide better service to customers. (3) When employees are treated reasonably and fairly by the organization and have positive job attitudes (job satisfaction and organizational commitment) and perceived behavior control, their spontaneous service-oriented organizational citizenship behavior is stimulated, thus increasing organizational development.